2016
DOI: 10.12717/dr.2016.20.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate and Hematological Responses with Temperature Changes of Red Spotted Grouper, Epinephelus akaara in South Korea

Abstract: The effect of sudden changes of water temperature (WT) on the survival rate and physiological responses of the red spotted grouper (Epinephelus akaara) were examined by manipulating WT control system for 9 days. Experimental condition was divided in two different regimes at low (from 10°C to 4°C, decreased 1℃/d) and high (from 28°C to 34°C, increased 1°C/d) WT. Survival rate of experimental fishes were observed, and determined the changes of hematological characteristics by analyzing plasma levels of cortisol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Accumulated thermal stress following declines of 12°C (from 26°C to 14°C) provoked increases in blood lactate (Lac) and glucose (Glu) levels, indicating that fish used all their physiological resources to maintain a high metabolic rate that might eventually have allowed them to escape to warmer habitat if such was possible. Blood Glu changes observed in N. cyanomos followed similar trends as those seen in the red spotted grouper Epinephelus akaara (habitat temperature range 11.7°-26.3°C) exposed to a temperature decrease from 10°C to 4°C at a rate of 1°C•d −1 (Park et al, 2016), and in the genetically modified farmed tilapia, Oreochromis niloticus (optimal temperature range of 26°-29°C) after 24 h exposure to 13°C (He et al, 2015). Umminger (1970) studied in detail the role of serum Glu in providing energetic fuel in the killifish Fundulus heteroclitus (habitat temperature range 6°-35°C) exposed to extremely low temperature (−1.5°C).…”
Section: No Compensation When Temperature Decreases Rapidlysupporting
confidence: 69%
“…Accumulated thermal stress following declines of 12°C (from 26°C to 14°C) provoked increases in blood lactate (Lac) and glucose (Glu) levels, indicating that fish used all their physiological resources to maintain a high metabolic rate that might eventually have allowed them to escape to warmer habitat if such was possible. Blood Glu changes observed in N. cyanomos followed similar trends as those seen in the red spotted grouper Epinephelus akaara (habitat temperature range 11.7°-26.3°C) exposed to a temperature decrease from 10°C to 4°C at a rate of 1°C•d −1 (Park et al, 2016), and in the genetically modified farmed tilapia, Oreochromis niloticus (optimal temperature range of 26°-29°C) after 24 h exposure to 13°C (He et al, 2015). Umminger (1970) studied in detail the role of serum Glu in providing energetic fuel in the killifish Fundulus heteroclitus (habitat temperature range 6°-35°C) exposed to extremely low temperature (−1.5°C).…”
Section: No Compensation When Temperature Decreases Rapidlysupporting
confidence: 69%
“…TP level is commonly used to diagnose fish health and disease, and its typically range is from ~4 g / dL to ~7 g / dL in fish (Yanagisawa & Hashimoto, 1984). When fish are under stress, the primary response increases the plasma cortisol, and the protein level increases as a secondary response (Davidson, Davie, Young, & Fowler, 2000). Abdelkahlek, Ghazy, and Abdel-Daim (2015) observed low levels of TP in fish under stress.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that physiological modifications in fish can impair both specific and nonspecific immunity, leading to a high incidence of diseases (Wendelaar- Bonga, 1997;Si et al, 2019;Ghorbani et al, 2021). On the other hand, stress encourages the synthesis of blood metabolites, including corticosteroids and catecholamines as well as the increased levels of oxidative stress markers in fish (Park et al, 2016;Stara et al, 2018;Shamohamadi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%